TOT Employability Skill Bagi Guru dan Siswa SMK - Fatwa Tentama; Desta Risky Kusuma; Surahma Asti Mulasari; Triwahyuni Sukesi; Sulistyawati Sulistyawati (Jurnal Pengabdian Pada Masyarakat, 2018)
EMPLOYABILITY SKILL TOT FOR TEACHERS AND STUDENTS OF VOCATIONAL HIGH SCHOOL. The issue of employability is a serious problem in Vocational High School today. The data show that the highest unemployment is dominated by graduate of Vocational High School. Vocational High School graduates who are not ready to work much become unemployed because they can not compete and get a job. In addition, when it was working will be difficult to carry out tasks in the work that eventually turned over. Teachers have difficulty in improving students' readiness because teachers do not have good employability skills so that teachers can not teach their students. TOT Employability is implemented with the aim to train students and teachers to become employability skill trainers. TOT Employability implementation method with lecture, game, role play and discussion methods. Participants in TOT Employability are students and teachers of SMK Negeri 1 Seyegan and SMK Negeri 1 Kalasan Sleman. The results of this program are students and teachers have good interpersonal communication skills, adaptability, cooperative ability, self-management ability, high entrepreneurship desire, independence, discipline, responsibility and motivation to learn high. Students and teachers who have good employability skills are expected to apply it to other students so as to have an impact on the overall employability capability.